Efficiency in estimating age through the Index Coronal Pulp Cavity in an adult population - Suárez-Ponce, Daniel (2016)
Objetive: Determine the efficiency of the method of estimating age based on the coronal tooth index. Materials and method: The method of index Cavity Coronal Pulp was performed on 432 teeth of the fourth mandibular quadrant (first premolar = 129, second premolar = 104, first molar = 113 and second molar = 86) evaluated in digital panoramic radiographs belonging adult individuals, aged 20 and 40, who attended the Imaging Department of the Faculty of Dentistry, National University of San Marcos and compared with the chronological age of the individual. Results: The results of the correlations were significant, especially for the second molars in males (r = 0.814, r2 = 0.663). Conclusion: The application of the method of dental coronary index is efficient and linear regression equation found larger sample approach in estimating the age of the individual.